Positional demands for various-sided games with goalkeepers according to the most demanding passages of match play in football - Andres Martin-Garcia; Julen Castellano; Antonio Gomez Diaz; Francesc Cos; David Casamichana (Termedia Publishing House, 2019)
The main aim was to determine the differences between four training games and competitive matches (CM) according to position and compared to the most demanding passages (MDP) of competitive match play. Global Positioning System data were obtained from 21 football players belonging to the reserve squad of a Spanish La Liga club during the 2015/16 season. The training games were small-sided games (SSGs) with 5 and 6 and large-sided games with 9 and 10 outfield players per team. The players were categorized based on positional groups: full back (FB), central defender (CD), midfielder (MF), offensive midfielder (OMF), and forward (FW). The variables recorded were the distance covered (DIS), DIS at high speed (HSR; >19.8 km•h-1), DIS at sprint (SPR; >25.2 km•h-1), high metabolic load distance (HMLD; >25.5 W•kg-1) all in m•min-1, average metabolic power (AMP; W•kg-1) and number of high-intensity accelerations (ACC; >3 m•s-2) and decelerations (DEC; <-3 m•s-2), both in n•min-1. The MDP was analysed using a rolling average method for AMP as a criterion variable, where maximal values were calculated for time windows of 5 and 10 minutes of CM and after that compared with the training game formats. As the SSG format increases, all the rest of the variables increase and the number of cases with significant interposition differences also increases (effect size [ES]: DIS: 0.7-2.2; HSR: 0.7-2.1; SPR: 0.8-1.4; HMLD: 0.9-2.0; AMP: 0.8-1.9; ACC: 0.8-1.7; DEC: 0.5-1.7). The large-sided game 10v10 + 2 goalkeepers over-stimulates sprint values relative to MDP (all: 121.0% of MDP, ES=0.5-1.8). This study provides useful information for coaching staff on the heightened impact of different training game formats on physical load, considering positional differences in relation to the MDP of competitive match play